(untitled) (AYUSHDHARA, 2024)
Diabetes stands as one of the most prevalent diseases globally, and diabetic patients are at risk of developing foot ulcers as a microvascular complication. These ulcers stem from diabetic neuropathy or atherosclerosis, leading to ischemia or breakdown of glucose-laden tissue, resulting in inflammation and ulceration. If left untreated, these ulcers can become infected, spreading to the underlying tissues. In Ayurveda, such ulcers are termed as Madhumehajanya Vrana. Sushruta Acharya outlined Anushastra Karma for managing Vrana, which includes Ksharakarma (application of alkalis) and Jalukavacharana (leech therapy). Kshara functions by actions like Chhedana, Bhedana, Lekhana and Ropana. Jalukavacharana possesses anti-inflammatory properties, promotes fresh blood supply by removing vitiated Dosha from the blood, and fosters wound healing by forming healthy granulation tissue. A 65-year-old female patient presented with a non-healing wound on the plantar aspect of her left foot below the greater toe since 8 months, associated with foul-smelling pus discharge for 6 months. She had a known history of diabetes mellitus since 10 years. The ulcer measured 4cm x 3cm x 2.5cm, GRBS was 380mg/dl with HbA1c of 12%. Patient was treated with Ksharataila infiltration, application of Tilwaka pratisaraneeya kshara followed by Lekhana of callosity present over the edges of the ulcer, and Jalukavacharana therapy for four sessions with seven days interval, in addition to internal medications. Glycemic control was achieved by Inj. Insulin Mixtard 30/70 30 units in morning and 15units at night.